2017
DOI: 10.30688/janzssa.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Under the Radar: The Mental Health of Australian University Students

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 25 publications
1
71
0
Order By: Relevance
“…We conclude this subsection by distinguishing between sustainable and current wellbeing as reported by certain researchers [34,41]. Sustainable wellbeing refers to general self-esteem and is concerned with the individual's own capabilities, self-image, and the academic concept of self as well as the student's social and emotional self-image.…”
Section: Students' Sustainable Wellbeingmentioning
confidence: 91%
“…We conclude this subsection by distinguishing between sustainable and current wellbeing as reported by certain researchers [34,41]. Sustainable wellbeing refers to general self-esteem and is concerned with the individual's own capabilities, self-image, and the academic concept of self as well as the student's social and emotional self-image.…”
Section: Students' Sustainable Wellbeingmentioning
confidence: 91%
“…Among all of the populations that suffer from mental disorders, students at the tertiary education level have a higher incidence of mental health problems -- including anxiety, depression, and other mental health conditions - than other age groups [ 5 ]. For instance, within Australia, a survey of over 3,000 students indicated that more than half reported high or very high levels of psychological distress, and one-third had thoughts of self-harm or suicide [ 6 ]. Many students experience academic stress and related performance expectations [ 7 ]; lack of social support networks, unfulfilled desires for friendship, and sexual harassment/assault [ 8 ]; worries over financial situation and imbalances between work and study; and higher likelihood of unhealthy lifestyles, including poor diet, alcohol use, and insufficient sleep [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is of concern, as failure to or a delay in seeking treatment can have serious consequences for people with mental health concerns, and studies have shown that the longer the duration of untreated depression, the poorer the outcomes of treatment 29 . In addition, for students, untreated mental health problems can impact negatively upon academic performance, course completion rates and may place students at a heightened risk of dropping out, with greater difficulty entering the workforce 30 . In addition, poor mental health among veterinary students may negatively affect the quality of services provided to clients and patients 31 …”
Section: Stress In Veterinary Studentsmentioning
confidence: 99%